Plant Extracts in Obesity: A Role of Gut Microbiota - Weng, Guangying; Duan, Yehui; Zhong, Yinzhao; Song, Bo; Zheng, Jie; Zhang, Shiyu; Yin, Yulong; Deng, Jinping (Frontiers in Nutrition, 2021)
Obesity has become one of the most serious chronic diseases threatening human health. Its occurrence and development are closely associated with gut microbiota, since the disorders of gut microbiota can promote endotoxin production and induce inflammatory response. Recently, numerous plant extracts have been proven to mitigate lipid dysmetabolism and obesity syndrome by regulating the abundance and composition of gut microbiota. In this review, we summarize the potential roles of different plant extracts including mulberry leaf extract, policosanol, cortex moutan, green tea, honokiol, and capsaicin in regulating obesity via gut microbiota. Based on the current findings, plant extracts may be promising agents for the prevention and treatment of obesity and its related metabolic diseases, and the mechanisms might be associated with gut microbiota.